(untitled) (Researcher: A Research Journal of Culture and Society, 2021)
This article has presented the difficulties and challenges faced by teachers in teaching English as a foreign language in Nepal. The main objective of the article is to describe the challenges in teaching English in the countries where it is not spoken as a mother tongue. The primary data were collected from three English teachers who have been teaching English in basic level at community schools located in Madhyapur Thimi Municipality, Bhaktapur. Field observation and in-depth interviews were the major tools for data collection. From the interviews and the available literature, some challenges of teaching English as a foreign language in our context have been drawn. The result shows that the teachers encounter the challenges inside the classroom with the knowledge of teacher and students, outside of it with parents and unfavorable environment, some challenges are related to languages and others are related to the curriculum, textbooks and the policy of the government. The findings of the study is beneficial to the teachers, researchers, school administrators, policy makers, curriculum developers and textbook writers to obtain the fruitful results in teaching English in Nepal.